Assessing the conservation values and tourism threats in Barrientos Island, Antarctic Peninsula. (15th July 2020) - Cajiao, Daniela; Albertos, Belén; Tejedo, Pablo; Muñoz-Puelles, Laura; Garilleti, Ricardo; Lara, Francisco; Sancho, Leopoldo G.; Tirira, Diego G.; Simón-Baile, Débora; Reck, Günther K.; Olave, Carlos; Benayas, Javier
Abstract: Antarctica has been witnessing continued growth of tourism, both in the overall visitation and in the diversity of itineraries and visitor activities. Expanding tourism presents unique business and educational opportunities, but it is also putting immense pressure on Antarctica's natural, and for the most parts, pristine environment. Understanding the effectiveness of different tourism management strategies and instruments, like the Visitor Site Guidelines adopted by the Antarctic Treaty, is fundamental to the sustainable management of Antarctic tourism. The purpose of this study was to assess the effectiveness of Visitor Site Guidelines and other tourism management actions in reducing impacts to the natural environment and for this, we used Barrientos Island as our case study as this is one of the most popular sites for tourism activities in the Antarctic Peninsula Region. First, we conducted a literature review and biological inventories to enable a thorough description of Barrientos Island's ecological values. The results show that Barrientos Island occupies the third highest biological richness among the top 15 most visited sites in the Antarctic Peninsula Region. We then assessed how tourism use on Barrientos Island affected biodiversity and the environment, and how Visitor Site Guidelines and other management measures helped alleviate these impacts. As intended, these instruments has been positive and valuable by providing operational guidance. However, they may lack significant information for tourism decision-making processes. To this end, we propose an alternative adaptive management approach that can more efficiently conserve biodiversity and environmental values while allowing the development of sustainable tourism activities in Antarctica. Highlights: Antarctic tourism is partially managed through Visitor Site Guidelines. Information regarding natural values of visited sites is very basic and tourism oriented. Filling ecological information gaps contribute to better inform management decisions. Sustainable tourism in Antarctic can be achieved through adaptive management. Specific studies and long term monitoring are necessary to manage tourism impacts.